Linear transceiver design for full-duplex multi-user MIMO system - Shenghong Li; Murch, Ross D.; Lau, Vincent K. N. (2014 IEEE International Conference on Communications (ICC), 2014)
We focus on a full-duplex multi-user MIMO system where the base station (BS) serves multiple uplink and downlink users simultaneously. Both the BS and the mobile stations (MSs) are equipped with multiple antennas. The performance of the system is limited by the self-interference at the base station and the interference caused by the uplink users on the downlink users. To address this issue, we propose to jointly design the beamformers of the BS and MSs. An optimization problem is formulated to maximize the weighted sum data rate subject to maximum power constraints. Although the problem is non-convex, it can be solved via iterative minimization of weighted sum mean square error (MSE), and a stationary point of the problem can be obtained. Strategies to choose uplink and downlink users and to determine initial point for the optimization problem are also proposed. Simulation results show that the weighted sum data rate achieved by full-duplex system is substantially higher than that achieved by baseline half-duplex systems.